Parallel processing for the real-time enterprise deploying web services on a solid platform for growth. - Derrick, John
Service orientation, web services, self-describing data, loosely coupled applications-choose your favorite term. The enterprise IT world is moving inexorably towards architectures that will allow rapid development of applications that provide real differentiated value to their businesses.